Investigation of synthethic diesel fuels and combustion characteristics using rapid compression machine (RCM) - Abdullah, Iqbal Shahridzuan (2022)
In a compression ignition engine, the fuel/air mixing process affects the combustion process. The study mainly investigates the effects of blending ratio, injection pressure (Pinj), and ambient temperature (Ti) on ignition delay and heat recovery process during the combustion process. The fuel was blended using a fuel blending machine at three different blending ratios of 10%, 15%, and 20% using the Tire Pyrolysis Oil (TPO) and Plastic Pyrolysis Oil (PPO). Each oil was tested by using a Rapid Compression Machine (RCM). The ambient temperature was varied from 750 K until 1050 K and Pinj at 80 MPa to 130 MPa. The data obtained was compared to Euro 5 as reference. The ignition delay of TPO10 was 1.61 ms at 80 MPa compared to 0.9 ms when the pressure was 130 MPa. For Ti, the ignition delay of PPO10 at 750 K reached 1.34 ms, but at 1050 K, the ignition delay shortened to 0.64 ms. Such increment in the Pinj and Ti helps in the atomization and combustible of mixture formation by lengthening the spray tip penetration, which also produces finer fuel droplet spray and reduces ignition delay. Whereas, the increase in blending ratio is found to increase the ignition delay while the increase in Ti and Pinj decrease the ignition delay, hence improving the combustion’s performance. The increment in ignition delay increases the mixing time available, which usually results in a more uniform mixture, substantial reductions in the overall cylinder pressure, and maximum HRR.